Personal Identity and Its Significance in the Context of Property Law - Klimaitė, Gerda (Teisė, 2025)
This article presents the concept of personal identity, introducing the essential foundations that constitute the construct of personal identity. The significance and importance of personal data in establishing personal identity is examined. The moment of acquiring the right to personal identity is analyzed. After evaluating the different traditions of legal systems, the concept of property rights is examined, and its connection to personal data is established. By using relevant European Union documents, the article assesses whether property rights to personal data are possible in the European Union.